2010
DOI: 10.1007/s12170-010-0092-x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Cardiovascular Disease Risk in Black People of the African Diaspora

Abstract: Insulin resistance plays a pivotal role in the development of cardiovascular disease (CVD) in whites. Insulin resistance syndrome includes a constellation of diseases such as hyperglycemia, obesity, hypertension, hypertriglyceridemia, and low high-density lipoprotein cholesterol. Black People of the African Diaspora (PAD) have greater rates of insulin resistance than whites, but the association of insulin resistance to CVD in black PAD is controversial. Moreover, among black PAD, the relationship of insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Furthermore, their total cholesterol concentrations were higher and HDL-C concentrations lower than those of their African counterparts. In accord with the THUSA study, we found more dyslipidaemia in the high AC Caucasian men ( Oosthuizen et al, 2002 ), but in contrast to literature, subclinical atherosclerosis was associated with dyslipidaemia in the high AC African men, who supposedly have less atherogenic lipid profi les than Caucasians ( Gaillard, 2010, Budoff et al, 2006. Augmented hs-CRP concentrations were reported to indicate a low-grade infl ammation in Africans ( Ntyintyane et al, 2009 ), and it has been found that African Americans have higher hs-CRP concentrations ( Watson and Topol, 2004 ), which may also be true for Africans in South Africa.…”
Section: Results ▼supporting
confidence: 89%
“…Furthermore, their total cholesterol concentrations were higher and HDL-C concentrations lower than those of their African counterparts. In accord with the THUSA study, we found more dyslipidaemia in the high AC Caucasian men ( Oosthuizen et al, 2002 ), but in contrast to literature, subclinical atherosclerosis was associated with dyslipidaemia in the high AC African men, who supposedly have less atherogenic lipid profi les than Caucasians ( Gaillard, 2010, Budoff et al, 2006. Augmented hs-CRP concentrations were reported to indicate a low-grade infl ammation in Africans ( Ntyintyane et al, 2009 ), and it has been found that African Americans have higher hs-CRP concentrations ( Watson and Topol, 2004 ), which may also be true for Africans in South Africa.…”
Section: Results ▼supporting
confidence: 89%
“…These findings may have important health implications given the emerging burden of CVD among urban black Africans and the fact that a three-fold risk of depressive symptoms has been observed in this population group in comparison with white Africans [6,13]. When coupled to their hypertensive status, these vasoconstrictive agent responses may underpin the increased long-term depression and vascular disease risk in urban Africans.…”
Section: Resultsmentioning
confidence: 90%
“…This increased prevalence is thought to be due to both genetic and environmental factors [65], although during adulthood the increased prevalence continues even after adjustment for lifestyle factors, suggesting that genetic factors may predominate [22]. Children and adults of Hispanic heritage are less likely to have hypertension, a tendency that may suggest underlying genetic causes, as it also persists even after adjustment for lifestyle factors [22].…”
Section: Ethnic Differences In the Metsmentioning
confidence: 99%
“…Children and adults of Hispanic heritage are less likely to have hypertension, a tendency that may suggest underlying genetic causes, as it also persists even after adjustment for lifestyle factors [22]. However, the clinical significance of these ethnic differences and their relationship with MetS is unclear, given that blood pressure has been frequently shown to have the weakest association with insulin resistance among MetS components [65,66]. …”
Section: Ethnic Differences In the Metsmentioning
confidence: 99%